2017
DOI: 10.1186/s12891-017-1684-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival of second biological DMARD therapy in patients with rheumatoid arthritis: a retrospective non-interventional cohort analysis

Abstract: BackgroundSince persistence to first biological disease modifying anti-rheumatic drugs (bDMARDs) is far from ideal in rheumatoid arthritis (RA) patients, many do receive a second and/or third bDMARD treatment. However, little is known about treatment persistence of the second-line bDMARD and it is specifically unknown whether the mode of action of such a treatment is associated with different persistence rates. We aimed to assess discontinuation-, re-initiation- or continuation-rates of a 2nd bDMARD therapy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
3
9
0
1
Order By: Relevance
“…Our results corroborate those of previous authors, who found that non‐TNFi drugs were associated with increased treatment persistence despite being prescribed less often (5,7,9–11,38,39). Although we reported lower drug costs for adherent swappers, as in other studies (7,8,10,11), we found that other categories of costs favored TNFi cycling.…”
Section: Discussionsupporting
confidence: 92%
“…Our results corroborate those of previous authors, who found that non‐TNFi drugs were associated with increased treatment persistence despite being prescribed less often (5,7,9–11,38,39). Although we reported lower drug costs for adherent swappers, as in other studies (7,8,10,11), we found that other categories of costs favored TNFi cycling.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study by Wu et al, assessing treatment patterns in PsA patients treated with bDMARDs (TNFi and non-TNFi) versus apremilast, authors reported a 33.3% switching rate at 2 years after treatment initiation in the bDMARDs cohort 15 the switching rate among PsA patients was 32.3% at 2 years in the current study. Similarly, the one year switching rate found in the current study among the subsample of RA patients (21.9%) is also generally in line with the rates reported in the literature, ranging between 11 and 18%, although closer to the upper end of the spectrum [19][20][21] .…”
Section: Discussionsupporting
confidence: 91%
“…Retention rates of second and third b/tsDMARDs are more difficult to compare with our current study, as there are few studies that have analysed similar data. Two available studies on RA have reported results similar to ours with second b/tsDMARD (TNFi) retention rates of 46–56% ( 50 ) and 56.8% ( 51 ). In the latter study, the TNFi (vs. non-TNFi) group had a lower rate (53.5 vs. 66.7%) and retention was similar for different episodes of use.…”
Section: Discussionsupporting
confidence: 86%